2021
DOI: 10.3389/fped.2021.658778
|View full text |Cite
|
Sign up to set email alerts
|

Diet Quality: A Neglected Parameter in Children With Food Allergies. A Cross–Sectional Study

Abstract: Background-Objective: With recent evidence suggesting that growth is no longer considered a major issue in children with food allergies (FA) on elimination diet, priority has shifted to diet quality to establish healthy eating patterns and prevent non-communicable diseases. The Diet Quality Index – International (DQI-I) could be useful for assessing the overall diet quality of FA-children. This study aimed to evaluate the impact of elimination diet on DQI-I in children with FA and the accuracy of DQI-I in refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 63 publications
2
3
0
1
Order By: Relevance
“…As seen in this study and previously identified, the moderation and balance components of the DQI-I identified poor dietary qualities related to chronic and non-communicable disease [ 45 ]. Where the limitation of the DQI-I lie is in capturing micronutrient deficiencies, especially those relevant to disease-specific states, as seen in the paediatric allergen elimination diets [ 45 ] and, in our case, frailty prevention in older people. To manage this limitation, we looked at a broader range of micronutrients and measures of energy intake.…”
Section: Discussionsupporting
confidence: 64%
“…As seen in this study and previously identified, the moderation and balance components of the DQI-I identified poor dietary qualities related to chronic and non-communicable disease [ 45 ]. Where the limitation of the DQI-I lie is in capturing micronutrient deficiencies, especially those relevant to disease-specific states, as seen in the paediatric allergen elimination diets [ 45 ] and, in our case, frailty prevention in older people. To manage this limitation, we looked at a broader range of micronutrients and measures of energy intake.…”
Section: Discussionsupporting
confidence: 64%
“…In a recently published study from the same geographical region, a small percentage (1.3%) of children with an established food allergy needed administration of a dosage of vitamin D above the recommended age-specific daily requirements to maintain the 25(OH)D level within normal range [ 31 ]. Baek and colleagues suggested that low serum vitamin D levels are associated with sensitization to food allergens [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, with the increase in the persistence and prevalence of FA and the emergence of new evidence regarding the interface between nutrition and the functioning of the immune system, there is growing concern about the quality of the diet of children and adolescents with FA. 13 …”
Section: Diet Quality and Immune Systemmentioning
confidence: 99%